ANALISIS RASIO SOLVABILITAS DAN RASIO AKTIVITAS UNTUK MENILAI KINERJA KEUANGAN PADA PT ANEKA TAMBANG Tbk PERIODE 2018-2022 - Rahma Noviyanti, Shintia; Sanjaya, Rudi (Journal of Research and Publication Innovation, 2024)
This research aims to analyze financial ratios in measuring financial performance at PT Aneka Tambang Tbk for the 2018-2022 period. This type of research is quantitative and qualitative descriptive and the data used in this research is secondary data, namely financial report data for 2018-2022. Based on research results, the Solvency Ratio, namely the debt to asset ratio, has an unfavorable performance of 37.376%, exceeding the industry requirement of 35%. Apart from that, the overall debt to equity ratio performed quite well at 60.346%, which is below the industry standard of 90%. Calculation of Activity Ratios with Inventory Turnover has a poor performance of 13,853 times below the industry standard, namely 20 times. Apart from that, total asset turnover also had poor performance at 1.048 times, this ratio is below the industry standard of 2 times.